ANALISIS KESALAHAN PENGGUNAAN â€œGENâ€, â€œTIAOâ€, â€œZHIâ€ PADA MAHASISWA PRODI PENDIDIKAN BAHASA MANDARIN FKIP UNTAN - Ningrum, Evi Widya; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractNomina Classifier is one of the most commonly classifier that are used in Mandarin, it is also the focused and one of the difficulty in Mandarin teaching. Nomina Classifier such as : â€œgenâ€, â€œtiaoâ€, â€œzhiâ€ are three words that commonly use in daily life as well. They have similarities and differences in semantics which make students often have errors in the use of Nomina Classifier. The writer analyzestudents errorsused the Nomina Classifier such as : â€œgenâ€, â€œtiaoâ€, â€œzhiâ€ and find out their causes. From the results of the test, the writer concludes that the error rate of using Â â€œgenâ€, â€œtiaoâ€, â€œzhiâ€ the error rate are : 51,65%, 47,45%, 52,47%. Student use the Nomina Classifier such as : â€œgenâ€, â€œtiaoâ€, â€œzhiâ€ the reason for the error is the mother tongue and the target language. The writer proposes teaching suggestions on the issues.Keywords :Nomina Classifierâ€œgen, tiao, zhiâ€error analysis